2014
DOI: 10.1155/2014/615109
|View full text |Cite
|
Sign up to set email alerts
|

Amides from Piper as a Diuretic: Behind the Ethnopharmacological Uses of Piper glabratum Kunth

Abstract: Several species of the genus Piper are known in Brazilian folk medicine as having diuretic activity. So, we propose to investigate the acute diuretic activity and the possible toxic effects of Piper glabratum Kunth, popularly known as false Jaborandi. Additionally, we propose to check whether there is any correlation between the biological activities of the crude extract (MEPG) and its 2-methoxy-4,5-methylenedioxy-trans-cinnamoyl-pyrrolidine (MMCP) in Wistar rats. The MEPG was fractioned by chromatography colu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The Piperaceae family is distributed in tropical and subtropical regions in the northern and southern hemispheres and comprises around 3600 species. The Piper genus constitutes the most represented, with around 2000 species [ 3 ]. In particular, biological properties of essential oils (EOs) from Piper aduncum L. ( Figure 1 ) have been widely studied, including antiprotozoal [ 4 , 5 ], anthelminthic [ 6 ], antioxidant [ 7 ], and insecticidal [ 8 , 9 ] activities.…”
Section: Introductionmentioning
confidence: 99%
“…The Piperaceae family is distributed in tropical and subtropical regions in the northern and southern hemispheres and comprises around 3600 species. The Piper genus constitutes the most represented, with around 2000 species [ 3 ]. In particular, biological properties of essential oils (EOs) from Piper aduncum L. ( Figure 1 ) have been widely studied, including antiprotozoal [ 4 , 5 ], anthelminthic [ 6 ], antioxidant [ 7 ], and insecticidal [ 8 , 9 ] activities.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Piper, popularly known as "falso-jaborandi" or "pepper plant", has been extensively studied for its potential pharmacological use, due to the presence of promising secondary metabolites. Among the biological effects and the popular use of the genus, the diuretic effect is highlighted [22]. Two species were the subject of more detailed experimental study to assess the possible diuretic effect: P. amalago L. and P. glabratum (Kunth) Steud.…”
Section: Brazilian Medicinal Plants With Diuretic Potentialmentioning
confidence: 99%
“…According to Novaes et al [23] the ethanolic extract of P. amalago leaves showed a diuretic effect at doses of 125, 250, and 500 mg/kg, associated with increased excretion of Na + and K + in the urine of NTR. Prando et al [22] investigated the effects of the methanolic extract of the roots of P. glabratum and the 2-me-thoxy4,5-methylenedioxy-trans-cinnamoyl-pyrrolidine compound isolated from the extract. However, the compound only showed significant diuretic effect at the dose of 30 mg/kg.…”
Section: Brazilian Medicinal Plants With Diuretic Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The essential oils from different Piper species commonly found in Brazil have been studied, and have showed a rich chemical composition, as well as biocidal, cytotoxic, antifungal, antioxidant, and anti-cholinesterase activities. [5][6][7] Among the Piper species native from Brazil, Piper glabratum Kunth has been little studied, despite its long use in folk medicine, and the studies that have pointed to its prominent diuretic proprieties, 8 as well as its antiparasitic activity against Leishmania and Trypanosoma cruzi. 9 Additionally, it has been showed that the essential oils possess anti-inflammatory potential and absence of toxicity.…”
Section: Introductionmentioning
confidence: 99%